2019
DOI: 10.1111/epi.16316
|View full text |Cite
|
Sign up to set email alerts
|

Both gain‐of‐function and loss‐of‐function de novo CACNA1A mutations cause severe developmental epileptic encephalopathies in the spectrum of Lennox‐Gastaut syndrome

Abstract: Objective Developmental epileptic encephalopathies (DEEs) are genetically heterogeneous severe childhood‐onset epilepsies with developmental delay or cognitive deficits. In this study, we explored the pathogenic mechanisms of DEE‐associated de novo mutations in the CACNA1A gene. Methods We studied the functional impact of four de novo DEE‐associated CACNA1A mutations, including the previously described p.A713T variant and three novel variants (p.V1396M, p.G230V, and p.I1357S). Mutant cDNAs were expressed in HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 50 publications
6
70
0
1
Order By: Relevance
“…Patient 1 and patient 2 harbored the same missense variant, C.4055G>A (p.R1352Q), which was reported previously (2, 5-7). The missense variants in patient 4 and patient 5 were C.2137G>A (p.A713T) and C.4177G>A(p.V1393M), respectively, also reported previously (8)(9)(10)(11). Patients 3, 6, and 7 had novel missense variants, C.2102G>T (p.G701V), C.185A>G (p.Y62C), and C.5442T>G (p.F1814L), respectively.…”
Section: Cacna1a Variantssupporting
confidence: 77%
“…Patient 1 and patient 2 harbored the same missense variant, C.4055G>A (p.R1352Q), which was reported previously (2, 5-7). The missense variants in patient 4 and patient 5 were C.2137G>A (p.A713T) and C.4177G>A(p.V1393M), respectively, also reported previously (8)(9)(10)(11). Patients 3, 6, and 7 had novel missense variants, C.2102G>T (p.G701V), C.185A>G (p.Y62C), and C.5442T>G (p.F1814L), respectively.…”
Section: Cacna1a Variantssupporting
confidence: 77%
“…In addition, Cacna1a S218L mice homozygous for the mutation develop multiple, spontaneous, tonic clonic seizures and die from sudden unexpected death in epilepsy (SUDEP) [48]. Recently, Jiang and colleagues [49], have demonstrated that both gain-and loss-of-function Cacna1a mutations are associated with developmental epileptic encephalopathies.…”
Section: Discussionmentioning
confidence: 99%
“…There are also S6 mutations in Cav2.3, the neuronal R-type channel encoded by CACNA1E, that causes developmental and epileptic encephalopathies (DEE) [68]. There is also recent evidence for de novo S6 mutations in CACNA1A, encoding the neuronal P/ Q-type Cav2.1 channel, linked to severe DEE with intellectual disability and variable motor symptoms [78]. All these S6 missense mutations share functional features: they significantly impair the inactivation properties of the affected Cav channels, likely promoting increase in intracellular Ca 2+ concentration and the subsequent cellular damages caused by abnormal Ca 2+ homeostasis [96].…”
Section: Discussionmentioning
confidence: 99%